(untitled) (Research, Society and Development, 2022)
The physical appearance of the one reflected through an attractive human being is attractive to the eyes and to the Cosmetic Industry. To develop a new skin care need, a rigorous evaluation of all components present. Cosmetic products must and must not present any risks to humans in normal situations or when used in a predictable manner. Therefore, in vitro tests to be an alternative for evaluating the safety of cosmetic products, since in vivo tests the inconveniences. Thus, this research sought to review the importance of applying in vitro tests in ensuring the safety of cosmetic products. Where used as a methodology bibliographic research of data from the integrative review in the databases of the Virtual Health Library and PubMed using the insertion of DeCS: Cosméticos, In vitro, Segurança; Cosmetics, In vitro, Safety; Cosméticos, In vitro, Seguridad; combined with the Boolean operator AND to perform the searches. After inclusion and exclusion, 8 articles were selected for discussion. The results of this review show the application of in vitro tests in evaluating the safety and efficacy of a pesticide-free lice treatment, verification of cytotoxicity when compared to retinol, investigation of hydroquinone depigmentation research, use to learn genotoxicity of some chemical products, among others. Concluding that the in vitro methods are a viable alternative, which guarantees the safety of the products.